Effects of increasing NDF from either dried distillers grains with solubles or wheat middlings, individually or in combination, on the growth performance, carcass characteristics, and carcass fat quality in growing-finishing pigs - Asmus, M.D.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 288 pigs (PIC TR4 × 1050, initially 83.6 lb) were used in an 87-d study to determine the effects of increasing dietary NDF from wheat middlings (midds) and dried distillers grains with solubles (DDGS) on growth performance, carcass characteristics, and carcass fat quality of growing-finishing pigs. Pens of pigs were randomly allot- ted by initial weight and gender (4 barrows and 4 gilts per pen) to 1 of 6 dietary treatments with 6 replications per treatment. Treatments were arranged in a 2 × 2 factorial plus 2 additional treatments with the main effects of added wheat middlings (0 or 19%) or DDGS (0 or 30%) to corn-soybean meal-based diets. The additional treatments were a diet containing 9.5% midds and 30% DDGS and a diet containing 19% midds and 15% DDGS. These combinations of midds and DDGS provided diets with different NDF concentrations ranging from 9.3 to 18.9%. Diets were fed in 4 phases. Choice white grease (CWG) was added to the diets to maintain similar ME in all diets within each phase. The only DDGS × midds interaction was a trend for carcass yield (P = 0.09). Adding either midds or DDGS to the diet reduced carcass yield by a similar magnitude, but the effect was not additive. Overall, (d 0 to 87), adding midds to the diet decreased (linear, P < 0.01) ADG, final BW, and HCW, and worsened (linear, P < 0.001) F/G and jowl iodine value (IV). Increasing DDGS did not influence growth performance or carcass traits except for an increase (linear, P < 0.001) in jowl fat IV. Pigs fed increasing NDF had decreased (linear, P < 0.05) ADG and HCW and poorer (linear, P < 0.02) F/G; however, these effects were driven by the pigs fed diets contain- ing midds and do not appear to be attributed solely to increased NDF levels. Increasing NDF also increased jowl fat iodine value, but increasing NDF with DDGS had a greater negative effect than increasing NDF through midds (due to the oil content of DDGS). Thus, increasing NDF has negative impacts on pig performance, carcass yield, and fat IV, but the effects appear to be more closely related to the individual ingredients used to increase NDF rather than NDF itself.
Keywords: Swine; DDGS; Fiber; NDF; Wheat middlings; Finishing pig